Karakteristik siswa dalam menyelesaikan masalah matematika menggunakan model pembelajaran polya - Mardiansa, Dwi Dion (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research is motivated by the problem solving ability of elementary school mathematics stories which still require proper and correct efforts. Especially in grade IV, appropriate and appropriate learning models are needed to improve students' problem-solving skills on math story problems. One of the learning models whose core is problem solving learning is the Polya learning model which is expected to be able to make students able to solve math story problems. The purpose of this study was to determine the effect of the Polya learning model on the ability to solve problems in mathematics story problems in fourth grade elementary school students in Surabaya. This research uses qualitative research. The method that will be used in this quantitative research is a case study using tests and observations to collect data. Based on data collection using tests and observations that show the ability to solve math story problems, fourth grade elementary school students in Surabaya can be trained through the Polya learning model.